ECONOMIC IMPORTANCE AND PHYTOSANITARY MONITORING OF FIRE BLIGHT - Călin SĂLCEANU; Mirela PARASCHIVU; Otilia COTUNA; Veronica SĂRĂȚEANU; Aurel Liviu OLARU; Ramona Aida PĂUNESCU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Fire blight (FB) caused by Erwinia amylovora, is a bacterial plant disease that poses a significant threat to pome fruit production worldwide. It can cause extensive losses in fruit yields, damage orchards and lead to trade restrictions on fruit exports. Fire Blight (FB) can also affect the longevity and productivity of fruit trees, further exacerbating the economic burden on growers and increasing management expenses. Because Erwinia amylovora is a regulated pest in most countries of the EPPO region its phytosanitary monitoring is mandatory in order to prevent the disease extension and new outbreaks. The inspections were required during the growing season (from after flowering until late summer), when the signs were obvious to find the disease. Thus, during 2022 a phytosanitary monitoring plan of Fire Blight was organized by Phytosanitary Office from Dolj County, Romania and the results emphasized that the apple area infected with Erwinia amylovora represents 3.85% from the total apple trees area (1,558 ha), 27% from the total surface of pear trees (36 ha) and 100 % for quince trees (2 ha). Comparatively with the results of Fire Blight monitoring realized previous year (2021), in 2022 was identified one new outbreak, but only for apple trees. Also, among all assessed trees (348) 260 trees include Malus domestica (apple). Among the measures applied for Fire Blight control the most effective were reducing the bacterial inoculum by manual removal of infected shoots and even uprooting of trees.